Higher Education Funding Strategies: Towards Equity, Efficiency, and Quality - Tinatin Gabrichidze (European Scientific Journal, ESJ, 2022)
As economists have become increasingly interested in higher education, economic reasoning has been applied, resulting in extremely useful research in higher education. With the growth of market forces in higher education, the changing role of government, and advances in research on the economics of higher education, higher education funding is increasingly seen as a tool to stimulate the market. The development of an effective funding strategy may be one of the keys to developing higher education - its quality and efficiency, increasing equity and equality. The article adds to the existing literature on higher education funding and the impact of market forces on higher education. It aims to provide an analysis of economic reasoning applied to higher education, which can be used as a tool to develop a funding strategy. It also includes an overview of different funding models concerning economic reasoning and synthesizes different funding strategies regarding their impact on the higher education market.